A new section for new voices (2025)
The journal, Nefrología Latinoamericana, is launching a new section in this issue dedicated to the voices of people living with kidney disease and the organizations that represent them. This editorial decision reflects the commitment of the Latin American Society of Nephrology and Hypertension (SLANH) to a more participatory, inclusive, and person-centered approach to medicine.